Campaign Message Design as Public Communication - Maskuri, M. Ibnu Naufal; Paramitha, Angella Dias (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
Convey message content in a wide range, the emergence of campaign messages accompanied by agencies or a number of groups who want to convey messages in the form of invitations or appeals messages to the wider community. Therefore, it is necessary to pay attention to the campaign message so that it does not distort the reading audience. The aim of this research is to see and understand how important message campaign design is as public communication based on effective message rules. The research method used in this research is descriptive qualitative, with a library research approach carrying out library exploration of written materials, whether in the form of notes, books or previous research. The results of this research show that to campaign a message to the public, you must pay attention to the types of campaigns that will be carried out, such as product-oriented campaigns, candidate-oriented campaigns, and ideology or goal-oriented campaigns. Apart from that, to help the message campaign be more easily accepted by the public, it is necessary to include message verbalization, visualization, illustrations, appeals, repetition and humor. There are 3 effective communication theories that can help the sustainability of message campaigns, namely using the Rhetorical theory of Aristotle (RTA), Extended parallel process model (EPPM), Social Cognitive theory (SCT) and symbolic convergence theory.